Head-to-Head Comparison of 68Ga-DOTA-TATE and 68Ga-DOTA-JR11 PET/CT in Patients With Tumor-Induced Osteomalacia: A Prospective Study - Hou, Guozhu; Zhang, Yuwei; Liu, Yu; Wang, Peipei; Xia, Weibo; Xing, Xiaoping; Huo, Li; Li, Fang; Jing, Hongli (Frontiers in Oncology, 2022)
Background The purpose of this study is to compare the sensitivity of 68Ga-DOTA-JR11 and 68Ga-DOTA-TATE PET/CT for detecting the responsible tumor of tumor-induced osteomalacia (TIO) and investigate if 68Ga-DOTA-JR11 PET/CT can identify the culprit tumor of TIO in multiple suspicious lesions in 68Ga-DOTA-TATE PET/CT. Methods A total of 19 patients with suspected TIO were prospectively recruited in this study. Each patient underwent whole-body PET/CT scan 40–60 min postinjection using 68Ga-DOTA-TATE and 68Ga-DOTA-JR11 on the same PET/CT, respectively in sequence, and on consecutive days. The diagnosis of TIO was confirmed by the combination of the postsurgical pathological results of the tumor and clinical information. Results Among the 19 patients with TIO who were included in this study, culprit tumors from all patients were confirmed pathologically. 68Ga-DOTA-TATE PET/CT positively identified the causative tumor in 18/19 patients, whereas 68Ga-DOTA-JR11 PET/CT was positive in 11/19 patients (94.7% vs. 57.9%, respectively; p < 0.05). 68Ga-DOTA-TATE PET/CT demonstrated more than one increased focal activity in 7 patients for a total of 16 lesions (3 lesions each in 2 patients and 2 lesions each in the rest 5 patients). However, seven of these 16 lesions showed concordant results on 68Ga-DOTA-JR11 PET/CT by demonstrating increased activity (one lesion in each of the 7 patients). The surgical specimens of the lesions in these 7 patients confirmed the phosphaturic mesenchymal tumor. A total of 11 culprit tumors were positive in both 68Ga-DOTA-TATE and 68Ga-DOTA-JR11 PET/CT. The SUVmax of 11 culprit tumors was significantly higher on 68Ga-DOTA-TATE PET/CT compared with that on 68Ga-DOTA-JR11 PET/CT (17.8 ± 12.5 vs. 6.8 ± 6.2; p < 0.05). Conclusions 68Ga-DOTA-TATE PET/CT is more sensitive to 68Ga-DOTA-JR11 PET/CT in the detection of the culprit tumor of TIO. However, 68Ga-DOTA-JR11 PET/CT might be helpful to identify the tumor in multiple suspicious lesions in 68Ga-DOTA-TATE PET/CT. Clinical Trial Registration clinicaltrials.gov, identifier NCT 04689893.